2017
DOI: 10.1680/jgeot.16.p.159
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lateral displacement induced by jet grouting in clayey soils

Abstract: The installation of jet-grouted columns in soft ground can induce lateral displacement resulting from injection of a great amount of water and grout into the ground, which may then lead on to further significant effects. This paper presents an approach to estimate the lateral displacement due to the installation of a jet-grouted column in clayey soils. Assuming that the installation of a jet-grouted column is represented by the expansion of a cylindrical cavity with a uniform radial stress applied at the plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(60 citation statements)
references
References 40 publications
0
60
0
Order By: Relevance
“…It should be noted that the method in the previous publication of the authors [19] is developed for analyzing the vertical jet grouting cases, but the authors found that Shen et al 's method cannot be directly used to obtain a reasonable displacement prediction for the horizontal jet grouting cases in engineering practice. Thus, a new approach is developed in this paper to provide a reasonable displacement prediction for horizontal jet grouting cases.…”
Section: Ground Displacements Induced By Installation Of a Row Of Colmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the method in the previous publication of the authors [19] is developed for analyzing the vertical jet grouting cases, but the authors found that Shen et al 's method cannot be directly used to obtain a reasonable displacement prediction for the horizontal jet grouting cases in engineering practice. Thus, a new approach is developed in this paper to provide a reasonable displacement prediction for horizontal jet grouting cases.…”
Section: Ground Displacements Induced By Installation Of a Row Of Colmentioning
confidence: 99%
“…Jet grouting is frequently used for the launching of shield machines or tunnel construction in complex geological conditions. Jet grouting technology is based on the injection of high velocity fluids through smalldiameter nozzles to erode the soil and mix it with injected grout to form a soil-cement column [16][17][18][19][20][21]. Based on the different methods of fluid injection, jet-grouting technology can be classified as (a) single fluid system (grout only), (b) double fluid system (grout + air), or (c) triple fluid system (water + grout + air) [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To sustainable urban development, geotechnical investigation, parameter selection, and structural design should be undertaken for such constructions. In future developments, before building construction, preventive measures such as geotechnical investigation and ground treatment, e.g., soil compaction, ground treatment, and piled foundation construction, may be necessary to improve the shearing resistance and stiffness of the existing ground [61,62]. Additionally, relevant regulations to prevent rooftop additions should be established to reduce potential damages to occupants in similar collapse events.…”
Section: Reasonable Monitoring Measuresmentioning
confidence: 99%
“…However, the negative influence of the strata grouting on the shaft lining is obvious and large [27]. Moreover, due to the grouting process is in the soil layer, the effect of the injection pressure on the shaft lining depends on the actual formation conditions and the treatment effect cannot be guaranteed [28,29]. It is necessary to establish a new method for the failure treatment which has the effect of the strata grouting and not the negative influence.…”
Section: Introductionmentioning
confidence: 99%